Burial Mound Ladies in southeastern Hallstatt area - Potrebica, Hrvoje (2010)
The paper discusses concepts of gender, age and status related to female burials under tumuli in the southeastern Hallstatt area, especially within the framework of the Kaptol Group and the Lower Carniola (Dolenjska) Group. It also discusses ritual concepts of weaving reflected in those burials.
Projekt MZOS
ENG